Determination of Distance Required to Ensure Stope and Footwall-drift Non-interaction Zone based on Geological Strength Index - Mehmet Volkan Ozdogan; Alper Gonen (Earth Sciences Research Journal)
In the Bakibaba Copper Mine, the longhole stoping method is used in the production of copper ore. Stability problems have occurred at times on the footwall drift due to the interaction between the footwall drift and stope. In this study, we propose a method for estimating the minimum distance necessary to ensure a non-interaction zone between the footwall drift and stope. We used the finite element method and various distances between the footwall drift and stope and the displacements over drifts as parameters. We also performed analyses on various geological strength index values from low to high to determine the effect of the rock mass on the interaction between the footwall drift and stope